2010
DOI: 10.1002/bjs.7072
|View full text |Cite
|
Sign up to set email alerts
|

Associations between leptin and adiponectin receptor upregulation, visceral obesity and tumour stage in oesophageal and junctional adenocarcinoma

Abstract: Obesity is associated with upregulated ObR and AdipR2 expression in oesophageal adenocarcinoma. The association of ObR and AdipR2 with tumour stage suggest that pathways involving adipocytokines affect tumour biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 45 publications
2
59
0
3
Order By: Relevance
“…The WC association with OAC was not attenuated when adjusted for BMI, adding to the evidence that abdominal fat is more important than just excess weight [O'Doherty et al 2012;MacInnis et al 2006;Corley et al 2007a]. Patients with OAC were also found to have significantly more VAT on CT compared with controls [Beddy et al 2010]. In a meta-analysis including data from six studies, when compared with normal body habitus, central adiposity was associated with higher risk of OAC (aOR 2.51; 95% CI 1.54-4.06) [Singh et al 2013b].…”
Section: Obesity and Oacmentioning
confidence: 84%
“…The WC association with OAC was not attenuated when adjusted for BMI, adding to the evidence that abdominal fat is more important than just excess weight [O'Doherty et al 2012;MacInnis et al 2006;Corley et al 2007a]. Patients with OAC were also found to have significantly more VAT on CT compared with controls [Beddy et al 2010]. In a meta-analysis including data from six studies, when compared with normal body habitus, central adiposity was associated with higher risk of OAC (aOR 2.51; 95% CI 1.54-4.06) [Singh et al 2013b].…”
Section: Obesity and Oacmentioning
confidence: 84%
“…Moreover, antiproliferative effects of phytoestrogens have been found in certain cell lines, including esophageal cancer cells [7,18,19]. Lignans can reduce expression of leptin and stimulate the expression of adiponectin [20], both of which in turn are inversely associated with the risk of adenocarcinoma of esophagus and gastroesophageal junction [21][22][23]. Taken together, these findings indicate that lignans have the potential to prevent esophageal cancer [24].…”
Section: Introductionmentioning
confidence: 99%
“…A number of in-vitro studies of adipokines have shown them to effect cellular proliferation, apoptosis, angiogenesis and inflammation [25-28]. In patients with OA there is obesity-associated upregulation of the leptin receptor (ObR) and adiponectin receptor 2 (AdipR2) [29]. Leptin and adiponectin have been shown to be associated with the risk of BO suggesting that adipokines may have a role in BO and OA [17, 30].…”
Section: Discussionmentioning
confidence: 99%